Nanoparticulate drug delivery perspectives on the transition from laboratory to market - Patravale, Vandana (Woodhead Pub., 2012)
Nanotechnology-based therapeutics, operating at scales of billionths of a metre, have great potential for future expansion in altering the scale and methods of drug delivery. The availability of these novel formulations to once-inaccessible areas of the body has greatly expanded the therapeutic window of existing drug molecules. Nanoparticulate drug delivery highlights and examines the transition of nanoparticulate drug delivery systems from the laboratory into a commercially viable sector. The first chapters of the book provide an overview of the use and characterization of nanoparticulate systems as drug carriers, including the assessment of their morphology, sterility and potential toxicity. In the latter part of the book, chapters cover nanotoxicology, regulatory aspect and clinical trials, ending with an overview of several case studies and a look towards future developments. Discusses the issues surrounding nanoparticulate products, based on personal experience of their formulationProvides an overview of new application areas, including RNA interferenceOutlines the pros and cons of nanoparticulate products, and discusses how these may influence their route into the commercial sector.
Keywords: Drug delivery systems.; Nanoparticles.; elektronické knihy; electronic books